Russian Society, Democratic Values, and the Legacy of the Early-1990s Economic Shock - Michael Alexeev; William Pyle; Jiaan Wang (Munich Society for the Promotion of Economic Research - CESifo GmbH, 2025)
Although it has been speculated that the pain and dislocation of the early 1990s left Russians with an abiding distaste for the values that animated the transition from communism, the quantitative evidence for a lasting effect is thin. Drawing on a large, regionally representative survey from 2010, we show that in regions where the embrace of liberal values declined most in the early 1990s, support for democratic values remained weakest a generation later. Instrumenting for the change in values in the early 1990s with variables that capture Soviet-era economic distortions, we connect the vulnerability of a region to the market liberalization shock of 1992 to its diminished support for liberal political values in both shorter and longer runs, particularly for the older cohorts who would have experienced the early 1990s as adults. The endurance of the effect of the early 1990s economic shock stands in contrast to research from other contexts that the attitudinal effects of economic shocks experienced after early adulthood are short-lived. We speculate that a possible explanation for why the effect of the early 1990s endures in Russia was the amplification of the economic shock by an "identity shock" related to Russia's post-imperial loss of status. In support of this hypothesis, we use multiple waves of the Integrated Values Survey (IVS) to show that in Russia, the demand for democratic values declined in the first half of the 1990s relative to other former communist countries, opening a values gap that persisted through at least 2017. Lastly, we draw on a recent survey experiment to show that respondents primed to consider the economic collapse of the early 1990s, and to a lesser extent the dissolution of the Soviet Union, are less likely to embrace democratic values than those in a control group.
Keywords: D72; D81; E32; P00; P20; 330; market transition; macroeconomic shock; democratic values; Russia